Frontline demonstration for boosting the oilseeds production in Rajasthan: A case study in Pali: FRONTLINE DEMONSTRATION FOR THE OILSEEDS PRODUCTION IN RAJASTHAN - M L MEENA; DHEERAJ SINGH (Journal of Oilseeds Research, 2013)
The oilseed crops grown in India are groundnut, rapeseed, mustard, sesame, sunflower, safflower, niger and soybean. The oilseed crops are well-distributed over different agro-climatic regionsin India. The major growing belt of oilseeds spreads from arid to semi-arid regions, covering large areas in Rajasthan, Punjab and Haryana, which contribute more than 37.9% of the total oilseed production in the country. This study was conducted in Pali district of Rajasthan during the years 2007 to 2010. The productivity of oilseeds crops continuesto be quite low due to gaps in adoption of oilseeds technologies. The yield of oilseeds can be increased by demonstrating their cultivation technologies at the farmers' fields under the supervision of scientists working in the operational area. Keeping the importance offrontline demonstrations, the KVK, CAZRI, Pali conducted demonstrations on improved agricultural technologies of oilseeds crops in farmers' fields during the year 2007-08, 2008-09 and 2009-10 and achieved the expected yields.